HUBUNGAN MANAJEMEN KONFLIK DAN MANAJEMEN RESIKO DALAM MENGEMBALIKAN EFEKTIVITAS TENAGA KERJA PT. BANK DANAMON INDONESIA TBK - Tantyo Setyowati dan Robi Pramana Putra (Fakultas Ekonomi Universitas Borobudur, 2015)
PT. Bank Danamon Indonesia Tbk, engaged in banking, the method used is a quantitative method through pembrongraman SPSS version 19.0. related to conflict management in dealing with conflicts that occur in the six main principles underpin the best practices of corporate governance in everyday operational activities such as integration, fairness, openness, accountability, commissioners, responsibility of commitment as a profession and independence with the application of such methods then the conflicts that occur in the company can be minimized. In the company's activities in anticipating risk management in daily bank operations are summarized in a number of categories such as credit risk, market risk or also known as price risk, liquidity risk, operational risk. The focus is on improving employee productivity through improving the quality of the work environment. The focus of Danamon's human resource development in this year is Culture and Employee Engagement, Leadership, Talent Management, Sourcing and Recruitment, Performance Management, to realize the effectiveness of the employees of Bank Danamon. Then based on the results of research obtained the results of multiple regression equation is Y = 20,781 + 0,659 X1 + 0,085 X2, Correlation (R) is 0,828, R Square equal to 0,686 whereas coefficient of determination (Adjusted R Square) from result of regression statistic output in this research got number equal to 0.674, this explains that the contribution given conflict management variables, and risk management on labor effectiveness of 67.4% while the remaining 32.6% influenced by other factors not examined in this study such as organizational climate, commitment, compensation , and others. Keywords : Conflict Management and Risk Management In Returning Labor Effectiveness